Associations Between Single-Child Status and Metabolic Syndrome in Children and Adolescents in China - Chen, Manman; Li, Yanhui; Chen, Li; Gao, Di; Yang, Zhaogeng; Ma, Ying; Ma, Tao; Dong, Bin; Dong, Yanhui; Ma, Jun; Hu, Jie (Frontiers in Pediatrics, 2021)
Objective: To evaluate the associations between single-child status and metabolic syndrome (MS) and to identify the highest risk group of MS among single children. Methods: Differences in participants' characteristics by sex were examined by Student's t-test for continuous variables and Pearson's chi-squared test for categorical variables. Multivariate logistic regression analysis was performed to estimate the odds ratios (OR) and 95% confidence intervals (CI) for MS and its components according to the single-child status. Radar maps were used to compare the composition of different components in MS. Results: In total, 11,784 (5,880 boys) children and adolescents were included in this study, with a mean age of (11.3 ± 3.1) years. MS was observed in 7.1% of participants, with a higher prevalence in boys (8.2%) than girls (5.9%) (P < 0.05). The prevalence of MS, elevated blood pressure and abdominal obesity in single children were higher than that in children with siblings, particularly in boys (P < 0.001). Elevated risk of abdominal obesity was observed in single children [boys (1.56, 95% CI: 1.31, 1.85), girls (1.40, 95% CI: 1.19, 1.63)], however, increased ORs of elevated blood pressure and metabolic syndrome were observed in single-child boys only (1.19, 95% CI: 1.01, 1.40 and 1.76, 95% CI: 1.34, 2.31, respectively). Results showed that a statistically significant association between single child status and MS was mainly observed in urban boys (2.04, 95% CI: 1.33, 3.12) and rural boys (1.50, 95% CI: 1.05, 2.15), but not in girls. Among all the combinations of MS, two combinations were significantly associated with the single-child status, including the combination of elevated blood pressure, abdominal and low HDL-C (1.45, 1.04, 2.04) and the combination of elevated blood pressure, abdominal obesity, low HDL-C and hypertriglyceridemia (2.04, 1.40, 3.06) (P < 0.05). Conclusions: The present study found that single children and adolescents had a higher risk of MS, elevated blood pressure and abdominal obesity. The associations were stronger in urban boys. Further attention should be directed to the prevention and control strategies targeting the high-risk population of MS.